Fresno County Women Lawyers Dinner with Patricia Shiu and Nancy DeStefanis - Watkins, Howard::::::::: (1987)
1986 Fresno County Women Lawyers President Doris Coleman speaking at lectern introducing California Women Lawyers' President Patricia Shiu